PENGHINDARAN PAJAK DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DIMODERASI OLEH MANAJEMEN LABA PADA PERUSAHAAN JASA KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2018 - Putra Utama Andra; Satriawan R. Adri; Mela Fito Nanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research will be conducted on financial services companies listed on the Indonesia Stock Exchange in 2014-2018. The purpose of this study was to determine the effect of related party transactions-receivable, party-related liability, institutional ownership, profitability on tax avoidance. And the effect of related party transactionsreceivables, related party transactions-liabilities and institutional ownership on tax avoidance with earnings management as the moderating variable. The population of this study were 39 financial service companies (excluding banking companies) listed on the Indonesia Stock Exchange in 2014-2018. The sample in this study was obtained by purposive sampling method, so that those who met the sample criteria were 31 companies. The method of data collection in this research is carried out by documentary methods, namely by studying, classifying, and analyzing secondary data in the form of independent auditor reports, financial reports, and other information related to the scope of this research. The analytical method used is multiple regression analysis. The conclusion of this research is that the profitability variable (X1) Related Party Transaction-Liability (X3) has no significant effect on tax avoidance. Variable Related Party Transaction-Receivable (X2) and institutional ownership (X4) have a significant effect on tax avoidance. Profitability variables (X1) and Related Party TransactionLiability (X3) after being moderated by earnings management are excluded from the equation because they do not affect tax avoidance. Variable Related Party TransactionReceivable (X2) and institutional ownership (X4) after being moderated by earnings management have a significant effect on tax avoidance. It can be seen that the coefficient of multiple determination (R²) is 0.674. This means that the profitability variable (X1), Related Party Transaction-Receivable (X2), Related Party Transaction-Liability (X3), institutional ownership (X4) after being moderated by earnings management affect tax avoidance by 67.40%. For this reason, it is recommended to add other variables to see the effect on tax avoidance such as the percentage of leverage, company size, board of commissioners and auditor reputation. The next researcher needs to consider separating by sector the sample of companies listed on the Indonesia Stock Exchange in order to get accurate results.Keywords: related party transactions-receivable, related party transactions-liabilities, institutional ownership, profitability and tax avoidance